1998
DOI: 10.1128/aem.64.4.1210-1219.1998
|View full text |Cite
|
Sign up to set email alerts
|

Self-Transmissible Mercury Resistance Plasmids with Gene-Mobilizing Capacity in Soil Bacterial Populations: Influence of Wheat Roots and Mercury Addition

Abstract: A set of mercury resistance plasmids was obtained from wheat rhizosphere soil amended or not amended with mercuric chloride via exogenous plasmid isolation by using Pseudomonas fluorescens R2f, Pseudomonas putida UWC1, andEnterobacter cloacae BE1 as recipient strains. The isolation frequencies were highest from soil amended with high levels of mercury, and the isolation frequencies from unamended soil were low. With P. putida UWC1 as the recipient, the isolation frequency was significantly enhanced in wheat rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0
4

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(49 citation statements)
references
References 40 publications
4
41
0
4
Order By: Relevance
“…In contrast, when analysing the e¡ect of mercury pollution in bulk and rhizosphere soils on the transfer frequencies in matings between the bacterial soil community and the rif r recipient strains Enterobacter cloacae BE1, P. £uorescens R2f and P. putida UWC1, increased transfer frequencies in the rhizosphere of young wheat with increasing mercury pollution were found by Smit et al [22]. With P. putida UWC1 as the recipient, transfer frequencies were signi¢cantly enhanced in the wheat rhizosphere in contrast to bulk soil.…”
Section: Capturing Of Self-transferable Mge Conferringmentioning
confidence: 86%
See 3 more Smart Citations
“…In contrast, when analysing the e¡ect of mercury pollution in bulk and rhizosphere soils on the transfer frequencies in matings between the bacterial soil community and the rif r recipient strains Enterobacter cloacae BE1, P. £uorescens R2f and P. putida UWC1, increased transfer frequencies in the rhizosphere of young wheat with increasing mercury pollution were found by Smit et al [22]. With P. putida UWC1 as the recipient, transfer frequencies were signi¢cantly enhanced in the wheat rhizosphere in contrast to bulk soil.…”
Section: Capturing Of Self-transferable Mge Conferringmentioning
confidence: 86%
“…Host range studies revealed a preference for hosts belonging to the L-and Q-proteobacteria. Despite the diversity seen by restriction pattern analysis the plasmids seemed to be related to each other based on hybridisation studies, and thus may share a rep gene distantly related to the IncA/C rep gene [22]. The preferential capture of Hg r plasmids from the rhizosphere of young wheat roots re£ects the dynamics of the plasmid hosts in response to plant growth.…”
Section: Capturing Of Self-transferable Mge Conferringmentioning
confidence: 89%
See 2 more Smart Citations
“…S3) that occurred only in D0 after 10 days incubation. These bands could be attributed to the development of populations that initially shared resistant/tolerant mercury traits or acquired them via mechanisms of gene transfer (Smit et al, 1998;Rasmussen and Sørensen, 2001).…”
Section: Diversity Affects Population Dynamics But Not the Functionalmentioning
confidence: 99%